Peningkatan HOTS pada Mata Pelajaran Green Chemistry Menggunakan Model Problem Based Learning - ELSYE DAMAYANTI, PINGKAN (LPPM Universitas Negeri Jakarta, 2024)
High-Ordered Thinking Skills (HOTS) are skills that must be possessed by students in the 21st century. To obtain good HOTS, a HOTS-based learning model is needed. State Senior High School (SMAN) 2 Jonggol, West Java, is one of the schools that has implemented the Independent Curriculum since 2020. The Independent Curriculum requires HOTS-based learning such as Project Based Learning (PjBL), and Problem-Based Learning (PBL). This means that SMAN 2 Jonggol has implemented HOTS-based learning. However, based on the results of interviews with chemistry teachers, students' HOTS was still low, indicated by students who tended to be passive and had difficulty concluding learning material. Therefore, this study uses a problem-based learning model to analyze the increase in HOTS in green chemistry material. This study uses the Classroom Action research method. The sampling technique in this study was purposive sampling, with a total of 42 students. The results of the Wilcoxon test have a Positive Ranks value at N of 42. This explains that there is an increase in student HOTS after using the problem-based learning model. So, it can be concluded that the problem-based learning model affects increasing students' HOTS skills.